Directed evolution of three-finger toxin to produce serine protease inhibitors. (June 2014) - Cai, Weiyan; Naimuddin, Mohammed; Inagaki, Hidetoshi; Kameyama, Kimihiko; Ishida, Norio; Kubo, Tai
Abstract Directed evolution is a very popular strategy for improving biophysical properties and even for generating proteins with novel functions. Recent advances in combinatorial protein engineering mean it is now possible to develop protein scaffolds that could substitute for whole antibody-associated properties as emerging therapeutic proteins. In particular, disulfide-rich proteins are attractive templates for directed evolution in the search for novel molecules because they can regulate the activities of receptors, enzymes, and other molecules. Previously, we demonstrated that functional regulatory molecules against interleukin-6 receptor (IL-6R) could be obtained by directed evolution of the three-finger toxin (3F) scaffold. In the present study, trypsin was selected as a target for directed evolution to further explore the potential use of the 3F cDNA display library. After seven rounds of selection, the DNA sequences converged. The recombinant proteins produced by the selected candidates had inhibitory activity against trypsin (Ki of 33–450 nM). Three of the six groups had Ki values that were comparable to bovine pancreatic trypsin inhibitor and soybean trypsin inhibitor. Two of the candidates also had inhibitory effects against chymotrypsin and kallikrein. This study suggests that 3F protein is suitable for the preparation of high-diversity libraries that can be utilized to obtain protease inhibitors. In addition to our previous successful targeting of IL-6R, the technique developed in our studies may have wide applications in the generation of regulatory molecules for targets of interest, such as receptors, enzymes for research, diagnostic applications, and therapeutic uses.